Dödsstraffet i USA - Martin Bergqvist (Nordisk Tidsskrift for Kriminalvidenskab)
In 1976, the United States Supreme Court concluded that capital punishment was constitutional, and since then 570 persons have been executed in the USA. The number of executions per year has increased substantially during the last decade, and there is reason to believe that the excessive use of the death penalty will continue.